2022
DOI: 10.1093/ofid/ofac617
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Infectious Diseases Risks From Dental Aerosols in Real-World Settings

Abstract: Background Infectious diseases physicians are leaders in assessing the health risks in a variety of community settings. An understudied area with substantial controversy is the safety of dental aerosols. Previous studies have used in vitro experimental designs and/or indirect measures to evaluate bacteria and viruses from dental surfaces. However, these findings may overestimate the occupational risks of dental aerosols. The purpose of this study was to directly measure dental aerosol composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“… The addition of PAC equipment to the already existing safety measures was found to be significantly effective in further microbiological risk reduction. Choudhary et al, 2022a , Choudhary et al, 2022b The bacteria identified were most consistent with either environmental or oral microbiota. Aerosols generating from dental procedures pose a low health risk for bacterial and likely viral pathogens when common aerosol mitigation interventions.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“… The addition of PAC equipment to the already existing safety measures was found to be significantly effective in further microbiological risk reduction. Choudhary et al, 2022a , Choudhary et al, 2022b The bacteria identified were most consistent with either environmental or oral microbiota. Aerosols generating from dental procedures pose a low health risk for bacterial and likely viral pathogens when common aerosol mitigation interventions.…”
Section: Resultsmentioning
confidence: 95%
“… Aerosols generating from dental procedures pose a low health risk for bacterial and likely viral pathogens when common aerosol mitigation interventions. Choudhary et al, 2022a , Choudhary et al, 2022b The number of particles: tip HVE > Conical HVE tip HVE > ISOVAC HVE Dentists should consider using HVE rather than standard-tip evacuators to reduce aerosols generated during routine clinical practice. Das et al 2022 The number of bacteria: no rinse group (control) > water (test) > 0.2% Chlorhexidine gluconate (test) > herbal mouthwash (test) 0.2% Chlorhexidine gluconate is superior in reducing the microbial load in aerosols produced during ultrasonic scaling.…”
Section: Resultsmentioning
confidence: 99%